2015
DOI: 10.1021/cg5018104
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Hydrogen Sorption in In-soc-MOF: A Charged Metal-Organic Framework with Open-Metal Sites, Narrow Channels, and Counterions

Abstract: Grand canonical Monte Carlo (GCMC) simulations of hydrogen sorption were performed in In-soc-MOF, a charged metal-organic framework (MOF) that contains In3O trimers coordinated to 5,5 -azobis-1,3-benzenedicarboxylate linkers. The MOF contains nitrate counterions that are located in carcerand-like capsules of the framework. This MOF was shown to have a high hydrogen uptake at 77 K and 1.0 atm. The simulations were performed with a potential that includes explicit many-body polarization interactions, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 83 publications
2
43
1
Order By: Relevance
“…This type of calculation was previously used to predict the rotational transitions for H 2 sorbed in various MOFs. 52,53,69,[71][72][73][74][75][76][77][78] Here, the results are discussed for calculations using the polarizable H 2 potential. For H 2 sorbed at site 1 in ZIF-68, a rotational energy level of 6.95 meV was calculated for the transition between j = 0 and the lowest j = 1 sublevel (Table S8).…”
Section: Rotational Dynamicsmentioning
confidence: 99%
“…This type of calculation was previously used to predict the rotational transitions for H 2 sorbed in various MOFs. 52,53,69,[71][72][73][74][75][76][77][78] Here, the results are discussed for calculations using the polarizable H 2 potential. For H 2 sorbed at site 1 in ZIF-68, a rotational energy level of 6.95 meV was calculated for the transition between j = 0 and the lowest j = 1 sublevel (Table S8).…”
Section: Rotational Dynamicsmentioning
confidence: 99%
“…This indicates that such INS features can be attributed to H 2 localized at these particular binding sites in MOF‐5. Overall, our group has successfully utilized MPMC to calculate the rotational transitions for H 2 adsorbed at different binding sites in numerous porous materials …”
Section: Featuresmentioning
confidence: 99%
“…Our aim with MPMC and MCMD is to leverage the best hardware available to date, increase the physical accuracy of traditional force field modeling through the inclusion of explicit, long‐range many‐body polarization in both the energetics and forces. We have used both codes in many published theoretical studies but have not formally introduced them until now.…”
Section: Introductionmentioning
confidence: 99%
“…Many of theoretical simulation calculation for hydrogen storage capacity determination of adsorbents realized by using Monte Carlo [25] method. It is reported that the Grand Cannonical Monte Carlo (GCMC) simulation calculations, which is an algorithm collection, had good correlation with the experimental results [26].…”
Section: Introductionmentioning
confidence: 99%